PERAN ORANG TUA DALAM MENINGKATKAN PRESTASI AKADEMIK ANAK: STUDI KUALITATIF TENTANG POLA ASUH DAN PEMBINAAN KELUARGA - Prasetyo, Teguh; Alya, Nurma; Rahmatillah, Fikhi (Jurnal Penjaminan Mutu, 2023)
This study aims to investigate the role of parents in improving children's academic achievement in Cimande Village. The family, as the smallest unit in society, has a significant responsibility in fostering a positive lifestyle for children, including resilience, strong personality traits, and a sense of responsibility. A qualitative approach was employed, utilizing interviews with parents of elementary school-level children in Cimande Village. Purposive sampling was used to select research participants, considering variations in parenting styles and family development. Thematic analysis was applied to analyze the collected data and identify emerging themes and patterns related to the role of parents in enhancing children's academic achievement. The findings indicate three key themes: the influence of good parenting practices and guidance on students' academic performance, the impact of parental attention to children's learning difficulties on their academic achievement, and the positive effect of active parental involvement in supporting their children's learning process. In conclusion, the research highlights the critical role of parents in enhancing children's academic achievement and their overall learning process. The family serves as an initial platform for laying the foundation and potential for children to comprehend essential concepts. The motivation and enthusiasm provided by parents have a positive impact on children's learning outcomes and foster their dedication to the learning process.